Justice beyond borders: the Operation Condor trial and accountability for transnational crimes in South America - Lessa, Francesca (International journal of transitional justice, 2015)
This article focuses on the so-called ‘Operation Condor’ trial currently taking place in Federal Criminal Tribunal 1 in Buenos Aires. The court is prosecuting human rights violations perpetrated across South America between the 1970s and 1980s against 106 victims - the majority Uruguayans, Chileans and Paraguayans. Those atrocities were committed within the framework of Operation Condor - a secret transnational network of intelligence and counterinsurgency operations set up by the dictatorships of Argentina, Chile, Uruguay, Paraguay, Bolivia and Brazil, targeting political opponents in exile. This article discusses the significance of this prosecution of transnational crimes in the region through interviews with prosecutors, lawyers, survivors and human rights activists, as well as attendance at trial hearings. It combines reflections from my personal experience as a researcher in the field with a preliminary evaluation of the trial's importance for transitional justice. (IJTJ/GIGA)